RESPON INDONESIA TERHADAP REZIM ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION (AATHP) (STUDI KASUS: KEBAKARAN HUTAN DI RIAU TAHUN 2018 – 2019) - Lasma Angel Apriana Girsang; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research is to know Indonesia’s response with the ASEAN Agreement on Transboundary Pollution (AATHP) regime in cases of forest fire in Riau Province in 2018 – 2019, where Indonesia as the main actor in cross-border smoke haze pollutions is in the spotlight in every forest fire that occurs in the Southeast Asia region. This research is utilized using neoliberal institutionalism theory by O. Keohane, constructivism perspective, non-traditional security concepts, and nation-state level of analysis. The method used in this research is a qualitative method with a descriptive model. This research data collection technique is through interviews and literature studies from several journals, books, documents, and websites. This research showed Indonesia's response to the ASEAN Agreement on Transboundary Haze Pollution (AATHP) regime reflects the characteristics of neoliberal institutionalism in terms of institutional formation, commitment to cooperation, policy making, and supervision. Within this framework, Indonesia seeks to build an effective regional cooperation mechanism to address the problem of transboundary haze pollution in Southeast Asia. Keywords: Neoliberal Institutionalism Theory, Human Security Concept, AATHP, Forest Fire